2000
DOI: 10.4141/a99-076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a beta-adrenergic agonist (L-644,969) on performance and carcass traits of growing lambs in a cold environment

Abstract: . 2000. Effects of a beta-adrenergic agonist (L-644,969) on performance and carcass traits of growing lambs in a cold environment. Can. J. Anim. Sci. 80: 459-465. A 2 × 2 factorial experiment was conducted to study the effects of the beta-adrenergic agonist L-644,969 (BAA, supplied at 0.28 vs. 0 mg kg -0.75 d -1 ) on growth performance, carcass traits and nitrogen balance of lambs at two environmental temperatures (0°C vs. 20°C). Sixteen Suffolk-Cross wether lambs (30.2 ± 2.06 kg BW) were randomly divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
1
18
2
1
Order By: Relevance
“…Quebec lamb production is very intensive with high ADG, producing lambs that are generally marketed before 5 mo of age. Therefore, the poor performance of lambs reported by Li et al (2000) and Moibi et al (2000) as well as the older age at slaughter in the latter study may not be relevant to current lamb production in Quebec. Schanbacher et al (1982) found better gains and feed efficiency and similar carcass composition with lambs raised at 5°C compared with lamb production at 18 or 31°C.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…Quebec lamb production is very intensive with high ADG, producing lambs that are generally marketed before 5 mo of age. Therefore, the poor performance of lambs reported by Li et al (2000) and Moibi et al (2000) as well as the older age at slaughter in the latter study may not be relevant to current lamb production in Quebec. Schanbacher et al (1982) found better gains and feed efficiency and similar carcass composition with lambs raised at 5°C compared with lamb production at 18 or 31°C.…”
mentioning
confidence: 71%
“…Raising lambs in such buildings may be economical since it has been estimated that in Quebec the cost of insulated and heated buildings is $42.32 m -2 more than uninsulated barns (Groupe Geagri 1998). Previous papers reported lower feed efficiency for 5-mo-old shorn lambs or lambs of unknown age (Li et al 2000) when raised at 0°C compared with 20 to 23°C. These lambs also produced more back fat at low ambient temperatures compared with lamb production at higher temperatures (Li et al 2000).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Este aumento en el rendimiento en canal coincide con los resultados de varios estudios en los que se empleó CZ (Vergara, (López et al, 2010;Romero, 2011) y básicamente se explica por la hipertrofia muscular originada por un aumento en la síntesis de proteína y una disminución en su degradación (Mersman, 1998;Beerman, 2002), lo que conduce a la reducción en el almacenamiento de grasa corporal (Yang y McElligott, 1989). No obstante esta explicación, se sabe que cada músculo responde de acuerdo con el tipo y la proporción de fibras que lo constituyen (Beerman, 2002), pues la ganancia es más evidente en las fibras tipo II y en las de tipo mixto oxidativo-glucolítico (Li et al, 2000).…”
Section: Resultados Y Discusiónunclassified